Doñana, need for adaptation: a new system as a sustainable assessment tool - Arnet-Callealta, Virginia; Sánchez-Fuentes, Domingo (Revista de Estudios Andaluces, 2024)
The resilience capacity of the Espacio de Doñana manifests the need to reinterpret the hegemonic codes of planning. For this, a new system is proposed based on a sustainable evaluation tool that is capable of provoking a complex territorial model that consolidates balanced sustainable standards in relation to the intensification of the use of the territory, its tourist exploitation and the protection of its natural heritage. Based on the theoretical-conceptual review on sustainability and territory of the study area, the design of a complex evaluation tool is proposed that redefines the current paradigm and through its contextualization allows detecting those parameters that are key to the change towards the new territorial model proposed.